POLA AKSESIBILITAS DI INSTALASI GAWAT DARURAT RUMAH SAKIT - , BERNI IDJI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In generally, the part of a hospital that handles of patients in critical condition or dangerous situation is called Emergency Department (ED). Emergency Department is a term used in the United States. Other common variations include 'Emergency Ward,' 'Emergency Center' or 'Emergency Unit'. In the UK and British Commonwealth countries the term used is an 'Emergency Room' or 'ER', 'Accident and Emergency' or 'A&E', 'Casualty', or 'Casualty Ward. In Indonesia there are three terms used. There are Instalasi Rawat Darurat, Instalasi Gawat Darurat, and Unit Gawat Darurat. In Indonesia, the term is more based on the type of hospital, but overall, it is essentially the same substance. It is referred of a service system that quickly and smoothly for all patients to be treated. Despite Emergency Department is part of an overall Hospital but it has a different character of service of another units in a Hospital. The main factor that distinguishes the Emergency Department from another unit is movement rapidity and smoothness of the patient, so that the risk of patient death or permanent disability can be minimized. The Emergency Department which handles of victims or patients in a state of emergency must have good access which provides ease of movement for all patients to enter and exit from this it. Accessible pathway is a factor that strongly support the service system in the Emergency Department. Emergency Department should have good access to provide ease of movement for the patient. The speed and smoothness of movement of the patients would be perfect if supported by good access. Through in deeply study which supported by the findings of the case and the data are accurate, the point is accessible for all patients involved in the Emergency Department has been formulated in a Pattern.